The comparison and diagnostic accuracy of different types of thermometers - Erdem, Nurettin; Koçak, Ülker; Pınarlı, Faruk Güçlü; Okur, Arzu; Derinöz, Okşan; Tapısız, Anıl; Baran-Aksakal, Fatma Nur; Cura-Yayla, Burcu Ceylan; Tezer, Hasan; Demirdağ, Tuğba Bedir; Bideci, Aysun (The Turkish Journal of Pediatrics, 2021)
Background. Fever is one of the leading causes of hospital admissions in children. Although there are many ways to measure body temperature, the optimal method and the anatomic site are still controversial. In this study, we aimed to evaluate the performance of new methods of measuring body temperature and to compare the accuracy, sensitivity and specificity of these methods. Methods. The body temperatures of the patients who were hospitalized as inpatients or who presented to the emergency room as outpatients between November 2014- March 2015 were measured and recorded. Mercury and digital axillary measurements, tympanic, temporal artery and non-contact skin temperatures were measured. Measurements were compared with each other. Results. According to our results temperature tends to increase over time for up to 8 minutes after placement when using axillary thermometers. Non-contact skin thermometers should be used only for follow-up of patients with fever, because of their low sensitivity and low negative predictivity. At the first examination, tympanic thermometers and axillary thermometers may be preferable for the diagnosis of fever. Conclusions. According to our results, using non-contact thermometers seems feasible and logical during the follow-up ofpatients with fever, but not in cases whose exact body temperature should be known. For the first examination of the patient to diagnose fever, tympanic thermometers and axillary thermometers may be preferable. Future studies are warranted to expose the optimum way of measuring body temperature in children.
Keywords: body temperature; pediatrics; thermometers